Os sentimentos na psicologia descritiva e analítica de Wilhelm Dilthey - Freitas, Fernando Patrick Prado de (2021)
This master's dissertation had the purpose of explaining the role of feelings in the psychology of the German philosopher Wilhelm Dilthey, having been based, above all, on his work “Ideas on a Descriptive and Analytical Psychology” (1894). More exactly, the questions that moved us were the following: what is the place, and what is the relevance, that feelings occupy within the structure and development of psychic life as conceived in the aforementioned work? In order to answer them, three stages were carried out: the first consisted of a preparatory moment, of a brief introduction to Dilthey's thought, in which he ended up pointing out the reason why he conceived the role of psychology as fundamental for the human sciences; the second stage consisted of explaining the proposal for a descriptive psychology (for which a certain contextualization was done), as well as the methodological discussion with the so-called explanatory psychology, culminating in the conception of experience; the third stage (and third chapter), finally, aimed to clarify the issues mentioned above (concerning feelings). This clarification came after initial considerations about psychic structure and processes (thinking, feeling, wanting) in their internal relationships. The results can be broken down into the following statements: feelings: a) are a co-originating constituent of the totality of psychic life, b) play a central role in the articulations and transitions of psychic processes and states, in addition to c) having a role also central in the development of psychic life. Decisive for outcomes b and c proved to be the intimate connection between feelings, vital-value, and structure: the course of transition of psychic states depends on how vital-value is affected in the reciprocal self-self-world relationship. Finally, there was a reflection on the hermeneutic relationship between psychic totality and psychic state, in order to highlight, in connection with the previous results, the primary aspect of reality as a reality of life that carries a total value